THE MAIN COMPETITIVENESS PROBLEMS OF AVIATION INDUSTRY IN RUSSIA - I. Bazikova (Вестник университета)
The main competitiveness factors aviation industry in Russia within the framework of the competitive diamond model proposed by Michael Porter have been considered. Aviation industry in Russia has the potential for further growth, but for its implementation it is necessary to modernize production, form the mechanisms for promotion, sales and after sales services of aviation products on the international and domestic markets, and to increase the priority of civil aircraft construction in comparison with military programs.